Further advances in implicit motor learning - Masters, R. S. W.; van Duijn, T.; Uiga, L. (Skill acquisition in sport: research, theory and practice, 2020)
It seems clear that the weight of evidence available in the implicit motor learning literature supports the utility of an implicit approach, but many questions remain unanswered. In future, for example, researchers need to establish better understanding of implicit motor learning by experts, as most of the evidence in the literature is generated from investigations of novices. It has been argued that experts make strategic use of conscious (explicit) attention to facilitate continued improvement of their skills. What, therefore, is the role of implicit learning in the skills of experts? Better understanding is also needed of the role of implicit learning in contemporary theories of motor learning, such as the constraints-based approach. These approaches have commonalities, such as the manipulation of constraints in the environment to influence motor learning. Further investigation is needed of the mechanisms that make implicit motor learning effective and potential new methods of implicit motor learning warrant testing. For example, rather than tDCS, can fatigue protocols be employed prior to practice to suppress working memory activity and thus restrain hypothesis testing? Or can altitude training be used, given that mild hypoxia suppresses working memory activity? For now, however, our knowledge of implicit motor learning in sport (and other domains) remains "in some raw fashion . . . ahead of the capability of its processor to explicate".